2021
DOI: 10.1021/acs.inorgchem.1c02199
|View full text |Cite
|
Sign up to set email alerts
|

Antiparallel Coupling between a 4f System and a Photoexcited Cyclic π System in a Dysprosium(III) Monoporphyrinato Complex

Abstract: Magnetic coupling resulted by an orbital angular momentum L of a photoexcited cyclic π-conjugated system and total angular momentum J of a localized 4f electronic system in [Dy­(TPP)­(cyclen)]Cl (TPP = 5,10,15,20-tetraphenylporphyrinato; cyclen = 1,4,7,10-tetraazacyclododecane) has been identified using magnetic circular dichroism (MCD). The MCD A-term patterns of the compound show a negative increment in the intensity by decreasing temperature and nonproportionality to the magnetic field. This phenomenon is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…Recently, we succeeded in the synthesis of lanthanide mono-TPP and mono-Pc complexes, [LnTPP(cyclen)]Cl, [LnTPP(L)]Cl and [LnPc(cyclen)]Cl (TPP 2− = tetraphenylporphyrinato dianion, L = 12-crown-4 and aza-12-crown-4, cyclen = 1,4,7,10-tetraazacyclododecane), 18,19 and reported investigations on the origin of the J – L interaction by the combination of MCD and ab initio calculations. 18 b ,20,21 These studies revealed that the origin of the interaction is essentially the interplay between the L of the photo-excited π electronic system L (π) and the other L from the orbital component of J of the 4f electronic system L (4f). Interestingly, so far, L (π) and L (4f) were found to be coupled in a ferromagnetic manner for terbium complexes, 18 b ,20 a ,21 while the antiferromagnetic manner was found in dysprosium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we succeeded in the synthesis of lanthanide mono-TPP and mono-Pc complexes, [LnTPP(cyclen)]Cl, [LnTPP(L)]Cl and [LnPc(cyclen)]Cl (TPP 2− = tetraphenylporphyrinato dianion, L = 12-crown-4 and aza-12-crown-4, cyclen = 1,4,7,10-tetraazacyclododecane), 18,19 and reported investigations on the origin of the J – L interaction by the combination of MCD and ab initio calculations. 18 b ,20,21 These studies revealed that the origin of the interaction is essentially the interplay between the L of the photo-excited π electronic system L (π) and the other L from the orbital component of J of the 4f electronic system L (4f). Interestingly, so far, L (π) and L (4f) were found to be coupled in a ferromagnetic manner for terbium complexes, 18 b ,20 a ,21 while the antiferromagnetic manner was found in dysprosium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…As for the values of L z , the four complexes studied in the present work as well as the three cyclen complexes previously studied have similar values for the B and Q bands, respectively. 15,28 This strongly suggests that the orbital angular momentum L z of the porphyrin is hardly affected by changes in the metal ion as well as the changes in the coordination atoms of the second ligand. In contrast, the value of Δ JL shows greater variance, indicating a large impact of the choice of the second ligand on the J–L interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Our group reported that in [Tb(TPP)(cyclen)] + , the Q(0,0) and Q(1,0) bands showed a ferromagnetic-type J – L interaction, while an antiferromagnetic-type J – L interaction was observed for the B(0,0) band, 15 in contrast to [Dy(TPP)(cyclen)] + , for which all the bands exhibited antiferromagnetic-type interactions. 16 Recently, we expanded our study for Tb heteroleptic complexes by changing the non-aromatic ligand. We reported that by replacing cyclen with 12-crown-4 ether or 1,4,7,10-tetraoxacyclododecane, a normal A-term spectral profile was observed for all three bands, and the intensity increased monotonically as the temperature was decreased, in contrast to the case of [Tb(TPP)(cyclen)]Cl.…”
Section: Introductionmentioning
confidence: 99%